Wake flow and flame characteristics in the porous media with different surface combustion states: An experimental study. (10th August 2022) - Suo, Shaoyi; Shen, Zhao; Shi, Junrui; Chen, Zhongshan; Zhang, Yanzhi; Jiang, Linsong; Zhang, Yang; Qi, Haotian; Xie, Maozhao
Graphical abstract: Highlights: A porous burner formed by SiC foam ceramic and alumina pellets is designed. The packed bed surface flame characteristics are captured by the high-speed camera. The wake flow fields under different combustion are analyzed by the PIV system. Combustion zone map as a reference for the industrial application is obtained. Abstract: A porous media burner composed of silicon carbide foam ceramic material and alumina pellets was developed to delve into the surface combustion. The surface flame characteristics under lean-burn conditions were captured with the high-speed camera. With the K-type thermocouples and the particle image velocimetry (PIV) method, the temperature distribution and the wake flow field in different combustion cases were analyzed. Moreover, by accurately regulating the inlet flow and the premixed equivalence ratio, the wide variety of flame forms are classified (e.g., the centered blue flame, the tiled blue flame, the tapered dark red flame and the tapered bright red flame). Lastly, the combustion zone map was generated to classify the mentioned variety of flame forms, which could be referenced to assess thermal characteristics for surface combustion.